Pelatihan Kurikulum 2013 dalam Meningkatkan Profesionalitas Guru SMP IT Jabal Noor, Medan Krio, Sunggal, Deli Serdang - Neliwati Neliwati (Universitas Islam Negeri Sumatera Utara, 2021)
ABSTRACT. The purpose of this community service was to train teachers how toimplement the 2013 curriculum. The target of this program was all teachers of JabalNoor Integrated Islamic Junior High School (called SMPIT) in Medan Krio,Sunggal, Deli Serdang North Sumatera. It was hoped from this program thatthe teachers are more professional in teaching and learning process. This programuses an active learning approach, where the participants involved must be ableto actively participate in activities and assistance in implementing the 2013curriculum. The results showed a change in mindset among 30 teachers aboutthe 2013 curriculum as an effort to encourage interactive learning. Amongthem, there are 25 people who are getting better at implementing the 2013curriculum in the following aspects:) curriculum ideas and designs, 2)approaches in the curriculum, 3) understanding in conveying curriculumconcepts. Meanwhile, 5 people need special guidance. Keywords: 2013 curriculum, Jabal Noor, teaching and learning process